2000
DOI: 10.1055/s-0037-1613979
|View full text |Cite
|
Sign up to set email alerts
|

Tissue Factor Is Rapidly Elevated in Plasma Collected from the Pericardial Cavity during Cardiopulmonary Bypass

Abstract: SummaryThere is growing evidence that the tissue factor/factor VIIa pathway of coagulation is enhanced during cardiopulmonary bypass. Hitherto, available evidence has suggested that upregulated monocyte bound tissue factor is made available, either in the blood collected from the site of surgery or on circulating cells. However, cellular upregulation is slow, while generation of factor VIIa in blood collected from the pericardial cavity is rapid. We have therefore investigated the possibility of an alternative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
0
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(48 citation statements)
references
References 23 publications
(36 reference statements)
3
44
0
1
Order By: Relevance
“…This is in line with previous studies by us and others [3,4,[8][9][10][11][12][13]. In addition, we showed that systemic concentrations of F 1+2 only increase during bypass in patients who receive retransfused pericardial blood.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This is in line with previous studies by us and others [3,4,[8][9][10][11][12][13]. In addition, we showed that systemic concentrations of F 1+2 only increase during bypass in patients who receive retransfused pericardial blood.…”
Section: Discussionsupporting
confidence: 93%
“…It is well established that pericardial blood is highly activated, including coagulation and fibrinolysis [3,4,[8][9][10][11][12][13]. In the literature, at least eight independent studies concluded that retransfusion of pericardial (wound) blood contributes to systemic coagulation activation [3,4,[7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The activation of factor VII by tissue factor is the initial step in the tissue factor pathway activation of the coagulation cascade [15]. Tissue factor binds with factor VIIa, stabilising the active site of factor VIIa.…”
Section: Our Study Adds Significantly To the Off-pump Literature Promentioning
confidence: 99%
“…Η έγχυση του µεσοθωρακικού αίµατος έχει σαν αποτέλεσµα την ενεργοποίηση της εξωγενούς οδού της πήξης [583,695,706], αν και η έκπλυσή του µπορεί να µειώσει αυτές τις ανωµαλίες [648,704]. Επιπλέον, το µεσοθωρακικό αίµα περιέχει µόρια λίπους και θροµβοέµβολα που δεν έχουν εντελώς αποµακρυνθεί από τα υπάρχοντα φίλτρα, και αυτές οι "προσµίξεις" έχουν ενοχοποιηθεί για τυχόν νευρολογική δυσλειτουργία µετά από καρδιοχειρουργική επέµβαση [432,707,708]. Η χρήση µιας συσκευής κυτταρικού διαχωριστή για έκπλυση του µεσοθωρακικού αίµατος έχει σαν αποτέλεσµα µια σηµαντική µείωση στα λιπώδη έµβολα και στις φλεγµονώδεις κυτοκίνες στο επαναχορηγούµενο αίµα σε σύγκριση µε το αίµα που λαµβάνεται απευθείας από την αναρρόφηση της καρδιοτοµίας [648,704,709].…”
Section: η άµεση επαναχορήγηση του µεσοθωρακικού αίµατος από τη µετεγunclassified